2013
DOI: 10.1039/c3cp52799a
|View full text |Cite
|
Sign up to set email alerts
|

Core–satellite Ag@BaTiO3 nanoassemblies for fabrication of polymer nanocomposites with high discharged energy density, high breakdown strength and low dielectric loss

Abstract: Dielectric polymer nanocomposites with high dielectric constant have wide applications in high energy density electronic devices. The introduction of high dielectric constant ceramic nanoparticles into a polymer represents an important route to fabricate nanocomposites with high dielectric constant. However, the nanocomposites prepared by this method generally suffer from relatively low breakdown strength and high dielectric loss, which limit the further increase of energy density and energy efficiency of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
78
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(88 citation statements)
references
References 54 publications
8
78
1
1
Order By: Relevance
“…However, to achieve high dielectric constants for nanocomposites, a high volume fraction of ceramic filler is normally required, which simultaneously decreases the flexibility of the nanocomposite. Moreover, breakdown strength drops off precipitously with the high proportion of ceramic fillers due to an increased defect density, agglomeration of fillers, as well as percolation with the low dielectric strength ceramic fillers [27]. That leads to very minor enhancement of energy-storage density as compared with the pure polymer matrix.…”
Section: Introductionmentioning
confidence: 98%
“…However, to achieve high dielectric constants for nanocomposites, a high volume fraction of ceramic filler is normally required, which simultaneously decreases the flexibility of the nanocomposite. Moreover, breakdown strength drops off precipitously with the high proportion of ceramic fillers due to an increased defect density, agglomeration of fillers, as well as percolation with the low dielectric strength ceramic fillers [27]. That leads to very minor enhancement of energy-storage density as compared with the pure polymer matrix.…”
Section: Introductionmentioning
confidence: 98%
“…In companies with such kinds of energy generation, energy storage technologies are urgently demanded for efficient utilization of the power produced from these renewable sources. [5][6][7][8] In recent years, towards the miniaturization, light weight and integration of electric and electronic devices, capacitors with high energy storage density are becoming distinctly important. 3 Capacitors which intrinsically possess a high power density and a fast charge/discharge capability are promising candidates for energy storage devices.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent studies have demonstrated that the morphology and geometry of ceramic nanoparticles influence the dielectric properties of nanocomposites222324. For 0–3 type ceramic-polymer nanocomposites, where spherical zero-dimensional ceramic nanoparticles are embedded in a three-dimensionally connected polymer matrix, a high volume fraction (>50 vol%) of nanoparticles is necessary to achieve a high permittivity nanocomposite.…”
mentioning
confidence: 99%